Developing the Professionalism of Islamic Religious Education (PAI) Teachers Through Learning Models - Tanjung, Erwin; Januri (LP3M UNZAH GENGGONG, 2025)
Learning is a systematic system consisting of various interrelated components. These components are: objectives, materials, methods, and evaluation. These four components must be considered in determining the learning model that will be used in learning activities. Learning models are arranged based on educational principles, psychological theories, sociology, system analysis and other theories. Learning models can be selected, meaning that teachers can determine the learning model that will be applied in the learning process according to the situation and conditions of the school environment to achieve learning goals. Teachers are currently required to develop according to their function, fostering, guiding and producing students to achieve educational goals. The development of curriculum, administration and equipment facilities must be balanced with the quality of teachers in carrying out the education process. Because in the entire education process, teachers are the main factor. So it is necessary to improve the quality and professionalism of teachers in carrying out the learning process, especially Islamic Religious Education learning where this can be done through mastery of learning models, so that the learning process can develop and not be monotonous.